Indicações geográficas e estratégia territorial competitiva : estudo comparado Brasil x Espanha - Silva, Antenor Roberto Pedroso da (2014)
The last two decades were marked by important economic and social changes in a global scope. The financial and commercial globalization, ally to the digital revolution , has been making easier the trade of information between culture, changing , in a subtle way, constant though, the worldwide feed habits . These transformations are bringing reflexes to the productive systems, marketing and logistics of the agribusiness products. It s being created the worldwide taste . Besides, in another way, a few phytosanitaries issues made the commercial walls , particularly by developed countries, using the feed security and the public health as justification. At this new scene, the firms starts looking for alternatives to get new consumers, and then, aggregate values to their products. In this moving, the work had the intention to show that, in special situations with some determinate product, the Geography Indication emerges as one of the alternatives to face the new reality. Search then, not only raises the income, but also the achievement of new markets, trough the singling of the products by the quality seals and accreditations. To reach the intended results, some hypotheses and problematic were noticed. The main one is that, in an international market subject by some amount of information, the competitor has a backdrop of a growing economic globalization. This globalization fiercer competition to reach the best market , that one which has the highest income and accept paying more for a product which offers the best quality to some determinate product. So, the unexceptional work, intended to inquire about the reasons that makes Brazil as a second position country in the world of the rural territorial brands, still being a big agricultural worldwide market player. Based in the analyses, all of them confirmed. It s not noted rude targeted incentives for promoting export and facing imports of value-added products through certifications, by the public s politics, the way we found through comparative study with Spain. In comparative studies, we noticed, still, the distance between our realities with the European s when analyzing the reality related institutions. Analyzing Brazil s fact, completely different than the found in Andalusia (Spain), perceives that the capital social and the representative organizations of agrarian interest s presence in Brazil are lower. Then, in Andalusia, the public politics supported by the social (rural) organization, has been supporting the producers to the achievement of their own accreditation products. Assesses that if there is a major concern of public servants and social workers for specific products in some territories, the IG may represent an important strategy of adding territorial income for rural production.